2012
DOI: 10.2737/rmrs-gtr-264
|View full text |Cite
|
Sign up to set email alerts
|

Climate change on the Shoshone National Forest, Wyoming: a synthesis of past climate, climate projections, and ecosystem implications

Abstract: The Shoshone National Forest (Shoshone) covers 2.4 million acres of mountainous topography in northwest Wyoming and is a vital ecosystem that provides clean water, wildlife habitat, timber, grazing, recreational opportunities, and aesthetic value. The Shoshone has experienced and adapted to changes in climate for many millennia, and is currently experiencing a warming trend that is expected to accelerate in the next century. Climate change directly and indirectly affects the Shoshone's high-elevation, mountain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…This approach has been used to assess vulnerability in California, the Rocky Mountain Region, and for several national forests in the Intermountain Region [40][41][42]. Other assessments relied on general literature review and synthesis [43]. A few assessments used methodologies specific to unique types of endpoints, including watersheds and socioeconomic endpoints [44,45].…”
Section: Participation Partnerships and Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been used to assess vulnerability in California, the Rocky Mountain Region, and for several national forests in the Intermountain Region [40][41][42]. Other assessments relied on general literature review and synthesis [43]. A few assessments used methodologies specific to unique types of endpoints, including watersheds and socioeconomic endpoints [44,45].…”
Section: Participation Partnerships and Processesmentioning
confidence: 99%
“…In developing assessments, authors intended to support improved decision-making in land management. As assessment documents and interviews with scientists highlight, many assessments were developed specifically to support upcoming forest-plan revisions in the focal regions [43,48]. Forest-plan revisions are a key venue for setting management direction for periods of a decade or more.…”
Section: Support For Application In Decision-makingmentioning
confidence: 99%
“…Changes in climate over the next century are anticipated to reduce groundwater recharge on a global scale (Rice et. al.…”
Section: Groundwatermentioning
confidence: 99%
“…Little quantitative information is available regarding the potential impacts of a changing climate on water resources in wilderness areas, although some studies have been completed for U.S. water resources in general. Rice et al (2012) indicated that a temperature increase of between 2 and 4 ºF (1 to 2 ºC) was observed in the Rocky Mountains of the western United States during the 20th Century. During the same period, researchers documented declines in precipitation and reductions in snowpack volumes.…”
Section: Potential Effects Of Climate Change On Wilderness Water Resomentioning
confidence: 99%
See 1 more Smart Citation